EFFECT OF DIFFERENT PLANTING DENSITY, IRRIGATION AND FERTIGATION LEVELS ON GROWTH AND YIELD OF BRINJAL (SOLANUM MELONGENA L.) - S. R. UGHADE; U. V. MAHADKAR1 (The Bioscan, 2015)
A field experiment was carried out during 2009-2010 at Department of Agronomy, Dr. B.S.K.K.V, Dapoli, Dist. Ratnagiri (M.S.) to study the effect of three planting densities (S1-75x75cm, S2-75-50x90cm and S3-175-50x50cm), three drip irrigation levels (I1-100 per cent, I2-80 per cent and I3-60 per cent of crop evapotranspiration) and two fertigation levels (F1-100 per cent and F2-80 per cent of RDF through drip) on growth and yield of brinjal. The results showed that the planting density S3 (175-50x50cm) recorded significantly superior growth parameters, biomass production, yield attributes and highest fruit yield (44.76 t ha-1). While the irrigation scheduled at I1 -100 per cent ETcrop noticed higher values of growth parameters, biomass production, yield attributes and maximum fruit yield (40.17 t ha-1). Similarly Fertigation level F1 100 per cent RDF through drip registered superior growth parameters, biomass production, yield attributing characters and fruit yield (39.63 t ha-1) as compared to fertigation level F2-80 per cent RDF through drip.